Abuse against people with Visual disabilities in the UAE society - Sayyari, Nahid; Alomosh, Ahmad (Al-Adab Journal, 2024)
The study aimed to investigate Abuse against people with Visual disabilities in the UAE society. To achieve the study's objectives, a quantitative approach was employed using a survey tool. The study was conducted on a purposively selected sample of 45 individuals with Visual disabilities from the UAE society. The study yielded several key findings, including that the highest age group represented was between 18-25 years old, with a majority being female. Most of the sample consisted of Emirati nationals with a bachelor's degree or equivalent education. Regarding forms of Abuse, an elevated incidence of harassment by other individuals towards people with disabilities was observed. The study also found statistically significant relationships between age, gender, social status, educational level, and abuse experienced by individuals with visual impairments. In terms of the consequences of abuse on individuals with visual disabilities, the most pronounced effect was a lack of trust in others.